Higiene Sanitation Management of Food and The Existence of Bacteria in The Food in RSUD Dr. Harjono Ponorogo - Titis jiastuti (JURNAL KESEHATAN LINGKUNGAN, 2018)
Hygienic and healthy food into the basic principles of the organization of food in hospitals. Food service hospital dedicated to the sick and at risk of pathogen contamination of germs. Implementation of food in the hospital must comply with Kepmenkes Decree No. 1204/Menkes/SK/X/2004 on Environmental Health Requirements Hospital. The purpose of this study is the management of food hygiene sanitation Identify at Hospital Dr. Harjono Ponorogo. This study is a descriptive observational. Object of the research officer food handlers, food hygiene, sanitation management, and food microbiological test (examination of E. coli and Salmonella). Collecting data using questionnaires, observation sheets, and test laboratory. Hygiene of food handlers who do not qualify the use of personal protective equipment, training of hygiene sanitation, and health screening. Sanitation management of food that does not qualify the quality of food, the food processing and presentation of food, while 9 samples prepared food laboratory test results 5 (55.6%) positive samples of E. coli. The conclusions in Hospital Dr. Harjono Ponorogo increase efforts to hygiene of food handlers and food sanitation management. Expected medical examination should be routinely expected 2 times a year, improving sanitation facilities that support the management of food hygiene, as well as water proofing regularly twice a year.